The Implementation of Contextual Teaching and Learning (CTL) to Improve Student Learning Outcomes and Activities on Social Studies Subjects in Class IV SDN Gambarsari II - Heni Rahmawati; Santy Widiani (PT FORMOSA CENDEKIA GLOBAL, 2023)
By Applying the CTL learning model, classroom action research offers benefits that allow students to produce content according to their understanding so that they can relate it to everyday life. The low student learning outcomes in the social studies class in class IV SD Negeri Gambarsari II are the first problem articulation, and the lack of student involvement in the IPS class in class IV SD Negeri Gambarsari II is the second. The research method used is classroom action research with a qualitative approach, which presents research data descriptively in the form of a presentation of the data studied. The results showed that 64.28% of students had acquired knowledge during the first cycle and 89.28% in cycle II. In other words, the CTL learning paradigm improves the ability of fourth-grade students in public elementary schools in the Gambarsari II social studies subject.